Enfoque ergonômico das condições de trabalho e saúde dos profissionais da estratégia saúde da família - Bizerril, Davi Oliveira (2017)
The Worker's Health is one of the fields of action of the Unified Health System responsible for the actions of epidemiological surveillance and health surveillance, promotion and protection of workers' health, as well as aiming at the recovery and rehabilitation of the health of workers submitted to risks and harms arising Conditions. In the Family Health Strategy, the workers of the family health team are subjected to several occupational risk factors in their work process within the work environment, having as one of the main ergonomics. The municipality of Fortaleza presents a characteristic framework of work situations that favors several ergonomic risks to the professionals of the team. The thesis aims to: analyze the ergonomic and psychosocial risks in the work process of the nurses and dental surgeons of the city of Fortaleza / CE (chapter 1); And to analyze the ergonomic risks of dental surgeons in the dental practice of the Family Health Strategy in the city of Fortaleza / CE (Chapter 2). This is a quantitative, descriptive, observational and cross-sectional study. The target population was composed of 414 professionals from the ESF of the city of Fortaleza / CE, among nurses and dental surgeons of 76 units of primary health care. As inclusion criteria, the professionals who were working at the UAPS for at least six months, and the criterion of exclusion was the professional withdrawal due to being involved in management, secondary care due to vacations, maternity leave or another reason. The data were tabulated and analyzed in the statistical program Statistical Package for Social Sciences 22.0 for Windows. In addition to the descriptive analysis, a bivariate analysis was performed. Data collection was performed through a structured questionnaire that addressed the following variables: socioeconomic and professional data; Ergonomic risks inherent in the attributions of the nurse and dentist of the family health team, ergonomic risks inherent in the clinical attributions of the dental surgeon of the family health team and the ergonomic situation of the FHS worker. The main ergonomic risks pointed out by nurses were: incorrect postures (56.2%), explicit and implicit pressure (31%) and imposed goals (30.5%). Those presented by CD were: incorrect postures (72.5%), repetitiveness of movements (47.5%) and maintenance of fixed posture (40.7%). The work situation analyzed was taken into account from the experience of the worker in the work environment, that is, from the professional in the primary health care unit. There was no improvement in the work process of the professionals. The units do not present themselves as safe environments for professionals, when it refers to occupational risks (64.9%) and to the professional and patient relationship (70.5%). In relation to postural ergonomics of dental surgeons during dental care, anterior positioning of the neck and head (83.8%), arms distanced from the trunk (46.1%), flexed cuffs (57.4%) and absence of Hand support (45.1%). Seventy-six percent of the participants reported that the primary health care units presented unfavorable physical structures regarding the positioning of dental equipment in the offices. Almost all dental surgeons (99.4%) who reported having acquired an occupational disease were from the statutory regimen. It is concluded that nurses and dental surgeons are subject to several ergonomic and psychosocial risks in their work process within the work environment. It was possible to verify that nurses reported as main ergonomic risks: incorrect postures, explicit and implicit pressure and imposed goals. The main ergonomic risks presented by dentists were incorrect postures, repetitive movements and maintenance of fixed posture. Dental surgeons showed that they respond with an incorrect posture: anterior positioning of the head, arms distanced from the trunk and flexed wrists.